Cervical High-Grade Squamous Intraepithelial Lesion Burden and Standard of Care Treatment Effectiveness and Safety in the United States, 2008–2018: The EACH-WOMAN Project. Issue 2 (23rd February 2023) - Hughes, Katherine C.; Herring, Timothy A.; Song, Jennifer N.; Gately, Robert V.; Przybyl, Lindsey M.; Ogilvie, Rachel P.; Simon, Keiko; Bhuyan, Prakash K.; Kyrgiou, Maria; Seeger, John D.
Abstract : Standard of care surgical treatment of cervical high-grade squamous intraepithelial lesions leads to substantial virological clearance but can be followed by recurrence, preterm birth, and complications including infection and bleeding. Abstract : Objective: Management of cervical high-grade squamous intraepithelial lesions (HSILs), the immediate precursor of cervical cancer, consists largely of surgical treatment for women at higher risk for progression to cancer. The authors' objective was to describe the occurrence of cervical HSIL in the United States and various outcomes for women who received surgical treatment. Methods: From a US commercial health insurer, a cohort of adult women with cervical HSIL diagnoses receiving surgical treatment within 3 months of diagnosis between January 2008 and September 2018 was identified. This cohort was followed for several outcomes, including cervical HSIL recurrence, human papillomavirus clearance, preterm birth, infection, and bleeding. Results: The incidence rate of cervical HSIL declined from 2.34 (95% CI = 2.30–2.39) cases per 1, 000 person-years in 2008 to 1.39 (95% CI = 1.35–1.43) cases per 1, 000 person-years in 2014, remaining near that level through 2018. Among 65, 527 women with cervical HSIL, 47, 067 (72%) received surgical treatment within 3 months of diagnosis. Among the women receiving surgical treatment, cervical HSIL recurred in 6% of surgically treated women, whereas 45% of surgically treated women underwent subsequent virological testing that indicated human papillomavirus clearance. Preterm birth was observed in 5.9% by 5 years follow-up and bleeding and infection each at 2.2% by 7 days follow-up. Conclusions: From 2008 through 2018, the incidence of diagnosed cervical HSIL decreased for several years before stabilizing. Surgical treatment of HSIL may be beneficial in removing the precancerous lesion, but cervical HSIL may recur, and the surgery is associated with complications including preterm birth, infection, and bleeding.